Independent Preoperative Predictors of Prolonged Length of Stay after Laparoscopic Appendectomy in Patients over 30 Years of Age: Experience from a Single Institution. Issue 11 (November 2016) - Wise, Eric S.; Gadomski, Stephen P.; Ilg, Annette M.; Bermudez, Camilo; Chan, Emily W.; Izmaylov, Michelle L.; Gridley, Samantha J.; Kaczmarek, Jessica V.; Melancon, Norman T.; Ahmad, Sarwat; Hocking, Kyle M.; Diaz, Jose J.; et al.
Prompt discharge after laparoscopic appendectomy (LA) is a marker of quality of care, fiscally desirable and feasible in select patients. Patients over 30 comprise a more heterogeneous cohort known to experience worse outcomes after LA. We aimed to identify easily available preoperative risk factors portending a postoperative length of stay ≥2 days among patients above age 30. In this investigation, 296 included patients from a single institution who underwent LA for acute appendicitis from 2010 to 2014 were retrospectively reviewed for preoperative demographics, laboratory studies, comorbidities, presentation characteristics, radiographic finding, and other rationally selected factors for association with postoperative length of stay ≥2 days. Bivariate and multivariate analysis was conducted to determine independent risk factors, which were subsequently modeled via receiver-operating characteristic curve generation and Kaplan-Meier analysis. "Classic" presentation [odds ratio (OR) = 0.5, P = .02], elevated red cell distribution width (RDW; OR = 1.5/% increase, P = 0.004) as well as evidence of rupture on CT (OR = 6.9, P < 0.001) were independently associated with postoperative length of stay ≥ 2 days. Modeling length of stay using these factors generated an area under the curve of 0.713 ± 0.037. Kaplan-Meier analysis of "classic" presentation, elevated RDW, and evidence of rupture on CT through the fifth postoperative day generated log-rank P values of 0.02, 0.05, and ≤ 0.001, respectively. In summary, lack of "classic" presentation, elevated RDW, and CT evidence of rupture are novel risk factors for prolonged postoperative length of stay in LA patients over 30. These findings may help target patients most appropriate for prompt discharge.